Glutamatergic Mechanisms for Speed Control and Network Operation in the Rodent Locomotor CPG - Talpalar, Adolfo E.; Kiehn, Ole (Frontiers in Neural Circuits, 2010)
Locomotion is a fundamental motor act that, to a large degree, is controlled by central pattern generating (CPG) networks in the spinal cord. Glutamate is thought to be responsible for most of the excitatory input to and the excitatory activity within the locomotor CPG. However, previous studies in mammals have produced conflicting results regarding the necessity and role of the different ionotropic glutamate receptors in the CPG function. Here, we use electrophysiological and pharmacological techniques in the in vitro neonatal mouse lumbar spinal cord to investigate the role of a broad range of ionotropic glutamate receptors in the control of locomotor speed and intrinsic locomotor network function. We show that non-NMDA and NMDA receptor systems may independently mediate locomotor-like activity and that these receptors set different speeds of locomotor-like activity through mechanisms acting at various network levels. AMPA and kainate receptors are necessary for generating the highest locomotor frequencies. For coordination, NMDA receptors are more important than non-NMDA receptors for conveying the rhythmic signal from the network to the motor neurons during long-lasting and steady locomotor activity. This study reveals that a diversity of ionotropic glutamate receptors tunes the network to perform at different locomotor speeds and provides multiple levels for potential regulation and plasticity.